Phytochemical analysis of extract from spontaneous fermentation of papaya leaf: article / Nurfatihah Md Jais and Mohamad Sufian So’aib - Md Jais, Nurfatihah; So’aib, Mohamad Sufian (2018)
In this study, phytochemical analysis was carried out on spontaneously fermented papaya (Carica papaya) leaf extract in terms of total phenolic content (TPC), total flavonoid content (TFC), and antioxidant activity. Moreover, the aim was to relate the presence of the metabolic compounds with the therapeutic benefits of the naturally fermented C. papaya leaf. Extraction method used solvent extraction by using methanol. Estimation of TPC and TFC used Folin-Ciocalteu’s reagent and aluminium chloride respectively, whereas antioxidant activity used DPPH and Trolox as radical and antioxidant models respectively. The results showed dissimilarity of TPC, TFC, and antioxidant activity of different samples taken at different sampling points throughout the 90 days fermentation period. The highest TPC and TFC were recorded at day 30 (79.84±0.29 mg GAE/g) and day 20 (51 ± 2.17 mg QE/g) respectively, whereas the highest antioxidant activity was recorded at day 30 (42.41 mM TE/g).